Understanding the Social Media Use in Tourism: An Affordance Perspective - Long Ting (Switzerland, 2022)
Social media are revolutionizing the way travelers prepare, experience, and complete the whole travel processes. Based on the technology affordance theory, this paper proposes an integrated affordance framework with the aim of understanding the functions that afford travelers’ social media use behavior in tourism. The empirical results indicate there are three categories of technology affordances in whole travel stages. Information gathering and collaboration constitute the first category of affordances, and they usually exist at pre-travel and in-travel stages. Additionally, self-presentation, content sharing, visibility, interaction, and persistence affordances are second category affordances, and they often occur at in-travel and after-travel stages. Whilst the communication and triggered attending affordances are seen as third category affordances, as they occur at all travel stages. This research contributes to the literature on the affordances of social media use in the whole processes of travel and offers practical implications for managing social media in tourism.
Well-Being in the Information Society. Fruits of Respect: 8th International Conference, WIS 2020, Turku, Finland, August 26–27, 2020, Proceedings